The duplicated Y-specific amhy gene is conserved and linked to maleness in silversides of the genus Odontesthes - Hattori, Ricardo Shohei (2019)
Sex-determining genes have been successively isolated in several teleosts. In Odontesthes hatcheri and O. bonariensis, the amhy gene has been identified as a master sex-determining gene. However, whether this gene is conserved along related species is still unknown. In this study, the presence of amhy and its association with phenotypic sex was analyzed in 10 species of Odontesthes genus. The primer sets from O. hatcheri that amplify both amhs successfully generated fragments that correspond to amha and amhy in all species. The full sequences of amhy and amha isolated for four key species revealed higher identity values among presumptive amhy, including the 0.5 Kbp insertion in the third intron and amhy-specific insertions/deletions. Amha was present in all specimens, regardless of species and sex, whereas amhy was amplified in most but not all phenotypic males. Complete association between amhy-homologue with maleness was found in O. argentinensis, O. incisa, O. mauleanum, O. perugiae, O. piquava, O. regia, and O. smitti, whereas O. humensis, O. mirinensis, and O. nigricans showed varied degrees of phenotypic/genotypic sex mismatch. The conservation of amhy gene in Odontesthes provide an interesting framework to study the evolution and the ecological interactions of genotypic and environmental sex determination in this group.